The ‘Dual Role’ approach: encouraging access to community radio. - Günnel, Traudel (Radio Journal: International Studies in Broadcast & Audio Media, 2008)
During the last two decades, community radio has achieved a legal status within the media system of many European countries. Although it is committed to 'giving a voice to the voiceless', one of its major weaknesses is a social and gender bias: many stations have difficulties in involving the target groups they aim to address, for example, women and so-called 'socially disadvantaged groups' (people with a migrant background, with limited school education, elderly people, homeless etc.). Strategies to involve those target groups seem to be missing. Drawing on the experience and the evaluation of three EU-funded projects, this article describes a training approach, which aims to encourage the involvement of disadvantaged groups in community radio. This consists of a learner-centred design, which links learning with doing: the 'dual role' of participants during the course, who are at the same time both trainees and also future trainers. The underlying theory of the approach – action oriented media pedagogy – is outlined and the role and importance of participatory evaluation (research) are discussed.